The pupil’s individual work skills’ development teaching mathematics at Lithuanian schools (5–9 decades of the 20th century) - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2003)
The article gives a profile on developing a system of individual tasks in mathematics by common efforts of specialists in didactics and highly experienced teachers. Initially individual tasks are classified on the basis of task performance end. As a result they fall into two basic groups: a) tasks for developing practical skills of the knowledge gained; and b) tasks for developing new knowledge skills. Further assignments are classified by the degree of creativity they require and fall into the following four groups: 1) reproductive exercises; 2) reconstruction exercises; 3) variation exercises; and 4) creative exercises.